2021
DOI: 10.1177/1049909120988506
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Health Literacy and End-of-Life Care Intensity Among Medicare Beneficiaries

Abstract: Background: Despite well-documented disparities in end-of-life (EOL) care, little is known about whether patients with low health literacy (LHL) received aggressive EOL care. Objective: This study examined the association between health literacy (HL) and EOL care intensity among Medicare beneficiaries. Method: We conducted a retrospective analysis of Medicare fee-for-service decedents who died in July-December, 2011. ZIP-code-level HL scores were estimated from the 2010-2011 Health Literacy Data Map, where a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…20 Individuals' behaviours toward ACP often appear to be shaped by their health literacy, which has been shown to affect their understanding of health challenges, their communication with medical professionals and their ability to make informed medical decisions. 21 22 Specifically, prior research showed that limited health literacy is associated with suboptimal self-care behaviour for diabetes, 23 poor health-related knowledge of chronic diseases, 24 communication gaps between patients and healthcare providers when discussing EOL care, 25 misunderstandings about EOL treatment options, 26 an increased probability of undergoing aggressive EOL care, 27 lesser engagement in ACP 28 29 and fewer chances of having an AD. 30 Moreover, health literacy has emerged as a pivotal factor in determining ACP engagement.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…20 Individuals' behaviours toward ACP often appear to be shaped by their health literacy, which has been shown to affect their understanding of health challenges, their communication with medical professionals and their ability to make informed medical decisions. 21 22 Specifically, prior research showed that limited health literacy is associated with suboptimal self-care behaviour for diabetes, 23 poor health-related knowledge of chronic diseases, 24 communication gaps between patients and healthcare providers when discussing EOL care, 25 misunderstandings about EOL treatment options, 26 an increased probability of undergoing aggressive EOL care, 27 lesser engagement in ACP 28 29 and fewer chances of having an AD. 30 Moreover, health literacy has emerged as a pivotal factor in determining ACP engagement.…”
Section: Bmj Public Healthmentioning
confidence: 99%
“…End-of-life health literacy is likely to be distinct from general health literacy due to the particular skills needed to navigate specific challenges of end-of-life planning and decision-making, such as exceptionally high stakes (questions of life and death), increased levels of risk and uncertainty, major emotional challenges related to the family and social contexts of dying, and complex discussions with highly-specialized professionals, potentially in a context of deteriorating physical and/or mental capacities. Poor end-of-life health literacy can lead to fewer palliative care visits, lack of advance care planning and advance directive completion, worse health status, lower quality of life at the end of life, and higher rates of unnecessary hospitalizations [10][11][12]. Improving health literacy related to end-of-life decision-making can thus support patient engagement and empowerment to make their own decisions in the face of death and potentially result in improved outcomes related to death and dying [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the SDH examined in the prior research are lack of health insurance (Elting et al, 2020), lower income (Tramontano et al, 2018), lower health literacy/education (Cross et al, 2021), and rural residency (Del Rosario et al, 2019). These factors resulted in poorer end-of-life outcomes, such as lower hospice enrollment (Elting et al, 2020), location of death different from patient preferences (Cross et al, 2021), and higher use of aggressive treatments (Luo et al, 2021). Regarding health literacy in particular, prior research found not only literacy on general health information/services but also literacy specific to end-of-life care, such as awareness or knowledge of hospice care, predicted attitudes toward the service and comfort with end-of-life discussion (Amjad et al, 2014; Cross et al, 2021).…”
Section: Introductionmentioning
confidence: 99%